Os Planos Nacionais de Educação 2001-2010 e 2014-2024: análise comparativa sobre as categorias sustentadoras das metas da Educação Infantil e do Ensino Fundamental - Micoanski, Marinês Limberger (2018)
This dissertation analyzes the categories that have been maintained and/or modified to support the concepts/arguments about the goals of Early Childhood Education and Elementary Education recommended in the National Education Plan (PNE) of 2014-2024 in relation to those recommended in the 2001 PNE-2010. The research was developed through a bibliographic and documentary survey and is organized in two chapters. In the first chapter, the objective was to understand the economic-social and political context of the 1990s, especially the elaboration of the National Education Plans 2001-2010 and 2014-2024. In the second chapter, the objective was to understand which categories were maintained and/or modified to support the concepts / arguments about the goals of Early Childhood Education and Basic Education in PNE 2014-2024 in relation to PNE from 2001 to 2010, in this way, to the research problem. The final considerations instigate reflection on the need to conquer a State policy for the materialization of the goals of the National Education Plan 2014-2024. The categories of the National Plans of Education 2001-2010 and 2014-2024, analyzed from the conception of Bakhtinian language, were conceived as historical-social products translated by statements arising from the interaction between socially organized subjects and for ideological purposes external to their immediate meaning. It expresses, in this case, the result of a dynamic and contradictory process of relations that do not explain themselves but only has meaning/meaning when constituents of the historical process of production of human existence. It is understood, therefore, that the statements of the Educational Policy documents, particularly the concepts/arguments present in the goals of Early Childhood Education and Basic Education in the PNE of 2014-2024 in relation to the 2001-2010 PNE, reflect and refract the reality heterogeneous in transformation. What can be understood from the analysis of the categories contained in the goals, articles and/or guidelines in relation to Early Childhood Education and Elementary Education is that much more than the quantitative record of the increase/reduction and/or the emergence of new ones, is that express a transformation of the discourses in the documents of Educational Policy, which followed the turn of the economicist bias toward humanitarian, from the 1990s. It can be verified that the concepts/arguments of the PNE 2014-2024 are linked to a project of society and education based on the following categories: prejudice; violence; discrimination; eradication of all forms of discrimination; social vulnerability; ethnic-racial inequality; human rights; protection of children, adolescents and youth; quality of education; evaluation.